Virtual Studio Learning Environment Based on STEAM Education Concept Integrated With Socio-Scientific Issues to Enhance Learner’s Scientific Creativity - Piboon, Kulchaya; Khlaisang, Jintavee; Koraneekij, Prakob (Journal of Information and Learning [JIL], 2024)
The objective of this research was to develop learners’ scientific creativity by incorporating a virtual studio learning environment based on the STEAM education concept integrated with socio-scientific issues. The learning environment highlighted features such as a showcasing space where learners can gain feedback, which could be useful for any revisions to increase the efficiency of their projects. This created room for learners’ trial and error while engaging in the activities. Moreover, the STEAM education concept integrated with socio-scientific issues was utilized in the activities. Using purposive sampling the sample consisted of 75 secondary school students. During the 8-week experiment, these students were assessed before (week 1), during (week 4), and after studying (week 8). The evaluation tools included a student self-assessment form and a teacher project evaluation form. Statistical analysis was conducted using mean, standard deviation, and repeated measure ANOVA. The results from the self-assessment form revealed that students had a higher average score for divergent thinking after studying (M = 4.66, SD = 0.22) than during (M = 3.31, SD = 0.23) and before studying (M = 3.02, SD = 0.36). For convergent thinking, the average score after studying (M = 4.65, SD = 0.23) was found to be higher than during (M = 3.32, SD = 0.22) and before studying (M = 3.02, SD = 0.37) at the .05 statistical significance level. The results from the teachers’ project evaluation form showed that the learners’ scientific creativity average after learning (M = 21.97, SD = 0.15) was higher than during (M = 18.23, SD = 0.15) and before learning (M = 12.53, SD = 0.11) at the .05 statistical significance level.